2011
DOI: 10.1558/jmea.v24i2.219
|View full text |Cite
|
Sign up to set email alerts
|

Mesolithic Cave Use in Greece and the Mosaic of Human Communities

Abstract: This paper discusses the Greek Mesolithic record in the light of refinements to the international calibration curve and recent archaeological research. Gentral to the discussion are the timefiame used for this period of Greek prehistory, and the diagnostic potential, or visibility, of Mesolithic stone tools. Rather than offering a comprehensive account of Mesolithic sites across Greece, this study focuses on a few known cave sites in the northwest, in order to bring out some less pronounced aspects of their ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…owski, 1982; Willis, 1994). In her review of the Mesolithic record in Greece, Galanidou (2011) suggested that rather than expecting a unifying picture and narrative of what Mesolithic groups were like, with some essential core of 'Mesolithicness', we should embrace a potential diversity of regional adaptations, 'more like a patchwork of patterns, colours and textures than a uniform design' (Galanidou, 2011: 231;see Boric, 2005). Galanidou also stresses that the frequent invisibility of Mesolithic sites may stem from a combination of factors that include our inability to differentiate diagnostic Mesolithic artefacts in those instances where these deviate from the expected norm (e.g.…”
Section: Problems In Mesolithic Archaeologies Of South-eastern Europementioning
confidence: 99%
“…owski, 1982; Willis, 1994). In her review of the Mesolithic record in Greece, Galanidou (2011) suggested that rather than expecting a unifying picture and narrative of what Mesolithic groups were like, with some essential core of 'Mesolithicness', we should embrace a potential diversity of regional adaptations, 'more like a patchwork of patterns, colours and textures than a uniform design' (Galanidou, 2011: 231;see Boric, 2005). Galanidou also stresses that the frequent invisibility of Mesolithic sites may stem from a combination of factors that include our inability to differentiate diagnostic Mesolithic artefacts in those instances where these deviate from the expected norm (e.g.…”
Section: Problems In Mesolithic Archaeologies Of South-eastern Europementioning
confidence: 99%
“…Until quite recently, Crete – the fifth largest island of the Mediterranean – was thought to have remained unoccupied until the foundation of an Initial Neolithic (IN) village at Knossos by migrant Anatolian farmers around 7000 cal bc (Broodbank and Strasser 1991; Cherry 1981, 43; Evans 1994). This late colonisation model was challenged in 2008 with the purported discovery of Mesolithic sites on the island's southern coast at Moni Kapsa and Plakias, an argument based on their stone tool assemblages closely resembling those from well-dated stratigraphic contexts on the Greek mainland (Galanidou 2011, 224; Strasser et al . 2010).…”
Section: Mesolithic Crete and Livari Skiadimentioning
confidence: 99%
“…Given the mixed nature of the Livari deposits, the microlithic- /flake- based assemblage can be dated only by reference to comparanda from elsewhere. The closest parallels come from nearby Moni Kapsa (Galanidou 2011, 224), and the Plakias region sites c. 180 km to the west (following the coast [Fig. 1]), assemblages that are similarly flake-based and microlithic, with ‘spines’, denticulates, notched and backed pieces well represented (Strasser et al .…”
Section: The Mesolithic Chipped Stone From Livarimentioning
confidence: 99%
“…The Aegean and Ionian regions are also emerging as a likely focus for initial attempts at sea crossings and early sea voyaging as documented by the colonisation or exploitation of offshore islands, extending back well before the spread of farming to at least 13,000 years ago and possibly earlier (Perlès 1979;Renfrew and Aspinall 1990;Kopaka and Matzanas 2009;Strasser et al 2010;Ammerman 2014). The site of Maroulas on the island of Kythnos (in the Cyclades) and stratum X at Knossos on Crete offer unequivocal evidence for maritime travels at around 9500 and 9000 years ago, respectively (Evans 1994;Efstratiou 2005;Sampson et al 2010;Galanidou 2011). Since the earliest points of arrival or departure, and the most favourable terrain for the establishment of settlements, are likely to have been located on or close to the seashore, especially on the smaller islands, much if not most of the relevant evidence for early sea voyaging must now lie underwater.…”
Section: Archaeological Contextmentioning
confidence: 99%